2015
DOI: 10.1038/srep13985
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Evaluation of Synergism between Anti-Tubercular Spectinamides and Non-Classical Tuberculosis Antibiotics

Abstract: Spectinamides are new semi-synthetic spectinomycin derivatives with potent anti-tubercular activity. The reported synergism of the precursor spectinomycin with other antibiotics prompted us to examine whether spectinamides sensitize M. tuberculosis to other antibiotics not traditionally used in the treatment of tuberculosis to potentially expand therapeutic options for MDR/XDR Tuberculosis. Whole cell synergy checkerboard screens were performed using the laboratory strain M. tuberculosis H37Rv, lead spectinami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…Otherwise, low doses of antibiotic may permit induction of resistance mechanisms (for example, subinhibitory concentrations of clarithromycin) and induces clarithromycin resistance in Mycobacterium tuberculosis in vivo. 31 The other major characteristic was noticed in terms of FAME production by planktonic cells and biofilm indwellers. FAMEs are extracellular enzymes produced by S. aureus and S. epidermidis, responsible for inactivation of bactericidal fatty acids by esterifying them to cholesterol.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Otherwise, low doses of antibiotic may permit induction of resistance mechanisms (for example, subinhibitory concentrations of clarithromycin) and induces clarithromycin resistance in Mycobacterium tuberculosis in vivo. 31 The other major characteristic was noticed in terms of FAME production by planktonic cells and biofilm indwellers. FAMEs are extracellular enzymes produced by S. aureus and S. epidermidis, responsible for inactivation of bactericidal fatty acids by esterifying them to cholesterol.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that improper use of antibiotics may result in induction of resistant bacteria. Bruhn et al 31 suggested that, after administration, antibiotic must reach the bloodstream and tissues in sufficient concentrations required for bacterial killing. Otherwise, low doses of antibiotic may permit induction of resistance mechanisms (for example, subinhibitory concentrations of clarithromycin) and induces clarithromycin resistance in Mycobacterium tuberculosis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…They noticed synergy with clarithromycin, doxycycline and clindamycin against clinical isolates. Further in vivo study of the efficacy of these combinations documented additional bacterial killing effect in a mouse model of acute tuberculosis infection, but not in a chronic infection model 62. In the study of Gonzalo, et al , amikacin in combination with doxycycline tested against clinical strains of Mycobacterium tuberculosis showed a synergistic effect in 18 of the 29 strains, and indifference in 11 strains 63.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that to achieve synergism in vivo, sufficient concentration of antibiotics in the bloodstream and infected tissues are important. The concentration of single drug of drug combinations is needed to have a longer half-life to prevent the induction of transient resistance mechanisms and the selection of genetic mutants [14]. Therefore, the pharmacokinetic profile of plant extract is needed for further study.…”
Section: Discussionmentioning
confidence: 99%